2004
DOI: 10.1007/s00467-004-1707-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular dysfunction in children with systemic lupus erythematosus

Abstract: Renal tubular and glomerular function was studied in patients under 18 years of age with childhood-onset systemic lupus erythematosus (SLE) in relation to disease activity in two groups: patients with clinical or laboratory evidence of lupus nephritis and those without (lupus non-nephritis). We reviewed 11 patients with lupus non-nephritis and 10 patients with lupus nephritis over a 12-month period. The measured glomerular filtration rates had a tendency to be lower in the lupus nephritis group. Glomerular dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Glucocorticoids alone or in combination with immunosuppressive agents may also be considered in cases of class I LN with podocytopathy on the electron microscopy (minimal change disease)63 64 or interstitial nephritis 65 66…”
Section: Resultsmentioning
confidence: 99%
“…Glucocorticoids alone or in combination with immunosuppressive agents may also be considered in cases of class I LN with podocytopathy on the electron microscopy (minimal change disease)63 64 or interstitial nephritis 65 66…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we believe that individual components should be examined separately. The significance of the TI compartment in LN disease has been a topic of much interest, and, for many years, authors have suggested that examination of the TI compartment might be useful for predicting outcome in LN [6,26]. Recently, studies of urinary biomarkers in LN kidney injury suggest that biomarkers may play a role in diagnosis and risk stratification of kidney damage [24,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Most published works on RTD are on adult patients 24–27 . A prospective study in children reported RTD as an earlier marker of lupus nephritis (LN) than albuminuria 21 …”
mentioning
confidence: 99%
“…2,3,8,15,[18][19][20] Published works on the extra-glomerular disease, namely tubulointerstitial nephritis (TIN), and vascular lesions like lupus vasculopathy (LV), thrombotic microangiopathy (TMA), vasculitis and arterio-/arteriolosclerosis are few. [21][22][23] Renal tubular function (RTF) is not routinely investigated in lupus patients in spite of the fact that SLE may be associated with varieties of renal tubular dysfunction (RTD). Most published works on RTD are on adult patients.…”
mentioning
confidence: 99%